(untitled) (Fiep Bulletin - online, 2012)
Introduction: Amputation is defined as the removal, usually surgical, of an entire member or a part of it. The amputation often occurs after all possible efforts to save an affected extremity. Amputations can occur for different causes, including vascular processes, neuropathics, traumathics, tumors, infectious and congenital. The transfemoral amputation refers to any amputation performed between the disarticulation of the knee and the hip. Aim: Identify which is the main transfemoral amputarion etiology in patients treated at FAG Rehabilitation Center. Methodology: It is a field study with an epidemic character, cross sectional and quantitative. The inclusion criteria are: being over 18 years old and have the cognitive preserved, perform services at FAG Rehabilitation Center and accept to participate in the research; 30 patients with tranfemoral amputation fit in the inclusion criteria and answered na interwiew with seven closed questions. At the end of the collecting the data were plotted and analyzed using SPSS 15.0. Results: It became evident that 73.3% of patients were male and 26.7% female. Checking the side of amputation there were 43.7% on the right side and 56.7% on the left side. The respondents’ average age was 57.8 (± 17.4) years old. Regarding the amputation level , it was predominantly medial. About the lower- limb transfemoral amputation etiology, 46.7% were from vascular causes, 43.3% from traumatic causes, 6.7% from tumors and 3.3% from congenital causes. Conclusion: It could verified at this study that the main transfemoral amputarion etiology occurred from vascular causes, with prevalence of male gender and assailing of the left member.